Working capital management and firm's profitability of listed construction firms in Malaysia/ Nurin Amalia Mohd Hidayat - Mohd Hidayat, Nurin Amalia (Faculty of Business Management, 2018)
Working capital management is a company's managerial accounting strategy that monitors and utilizes the main working capital component of the company, which are current assets and current liabilities. It is vital for a company to always check their working capital to make sure that company can maintain sufficient cash flow to meet its short-term obligations. Besides, with a proper working capital management, a company can reduce its risk of being in a bankruptcy state. Numerous findings mentioned that working capital management is negatively affects a firm's profitability. On the other point of view, some past researchers mentioned a positive relationship. Thus, there have been contradicting results between the past studies conducted by past researchers regarding this field. This research paper was carried out to observe the significant relationship between working capital management and firm's profitability. The main objectives of this paper are to identify and investigate the relationship between working capital management and firm's profitability of construction firms listed in Bursa Malaysia from year 2012 to 2017. As the firm's profitability will be the dependent variable; cash conversion cycle, liquidity, leverage, firm size and firm growth are the independent variables.